Opening windows for bone remodeling through a SLIT - Iqbal, Jameel; Yuen, Tony; Kim, Se-Min; Zaidi, Mone (The Journal of Clinical Investigation, 2018)
Bone formation and resorption are tightly coupled, and dysfunction of either process leads to bone diseases, such as osteoporosis. Bone-forming agents have been explored clinically to increase bone density; however, long-term efficacy of these strategies is limited due to the accompanying increase in resorption in response to increased bone formation. Axonal guidance molecules have recently been shown to regulate formation-resorption coupling and thus have the potential for osteoporosis therapy. In this issue of the JCI, Kim et al. demonstrate that osteoclast-secreted SLIT3 influences bone formation and resorption by promoting osteoblast migration and suppressing osteoclast differentiation. Activation of SLIT3/ROBO signaling in ovariectomized mice increased bone mass, suggesting that SLIT3 should be further explored as a therapeutic target.